2014
DOI: 10.1002/ajmg.a.36773
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fat overgrowth in Proteus syndrome

Abstract: Proteus syndrome is a rare, mosaic disorder with asymmetric and distorting overgrowth of the skeletal system, skin, and adipose tissues. Cardiac abnormalities are rare in this syndrome and only two prior cases have been reported. Many patients with PS followed at our institution underwent transthoracic echocardiograms for preoperative evaluation or as work-up for associated pulmonary disease. Some were noted to have prominent, focal echodense areas in the myocardium. We further investigated cardiac findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Informed consent was obtained from all the participants or their parents/legal guardian for minors (under the age of 18). A subset of the current study population was previously reported by Hannoush et al and Jamis-Dow et al 17 , 18 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed consent was obtained from all the participants or their parents/legal guardian for minors (under the age of 18). A subset of the current study population was previously reported by Hannoush et al and Jamis-Dow et al 17 , 18 .…”
Section: Methodsmentioning
confidence: 99%
“…All chest CT studies were evaluated on a PACS workstation (CareStream, Version 12.1.6.1005, Carestream Health, NY) independently by two readers who were fellowship-trained in thoracic and body imaging and who were aware of the Proteus syndrome diagnosis but were blinded to all other clinical information. The readers (A.S., 10 years of experience and E.B.T., 13 years of experience) evaluated the lungs, heart, pleura, thoracic vasculature, chest wall and mediastinum for cardiothoracic imaging findings that were previously reported in the literature (Supplemental Table S2 ) 7 , 12 , 14 18 , 21 23 . The entire thorax was assessed for the presence of nodules or masses suspicious for malignancy 8 , 17 and any other additional thoracic findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the denominator for PROS is larger, this suggests (but does not prove) that the risk of tumors is much higher in Proteus than in PROS. Further, we are not aware of myocardial fat overgrowth in individuals with PROS, whereas this is common in Proteus syndrome (Hannoush et al 2015). Other generalizations could be enumerated, but the point is that although both Proteus syndrome and PROS can display a wide range of severity, the nature and frequency of specific manifestations are distinct in the two syndromes.…”
Section: Discussionmentioning
confidence: 97%
“…The skin, bones, and adipose tissue are commonly affected. 2 The syndrome is a mosaic genetic syndrome that occurs de novo, with an estimated prevalence of less than one per one million. 3 Proteus syndrome can be associated with bony defects, epidermal nevi, vascular tissue malformations, adipose tissue dyregulation, and lungs abnormalities.…”
mentioning
confidence: 99%